Liberal arts catch-up revisited - Goyder, John (Canadian Journal of Higher Education, 2014)
This paper replicates the work of Giles and Drewes from the 1990s. They showed a catch-up effect whereby graduates of liberal arts undergraduate programs, although at an early-career disadvantage compared with graduates of applied programs, had higher incomes by mid-career. Working with the Panel 5 Survey of Labour and Income Dynamics (2005–2010), the catch-up no longer exists.